2013
DOI: 10.1177/0300060513489476
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium reversed by sugammadex versus mivacurium during high-risk eye surgery: An institutional anaesthetic practice evaluation

Abstract: Residual postoperative curarization at the time of extubation was frequently observed in group M, whereas there was complete recovery in group R/S. Reversal of NMB by sugammadex provides an additional safety dimension to patient care and should thus be considered especially for those at risk of airway complications or aspiration, in addition to frail patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Deeper levels of NMB resulted in more advantageous reversal times for sugammadex 14 . The incidence of postoperative RNMB with TOF ratios <0.9 or <0.7 was significantly lower in sugammadex-versus neostigmine-or non-reversed (timing) patients 14,16,17 . A significant correlation between RNMB and postoperative chest X-ray pathology was reported in one investigation 16 .…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Deeper levels of NMB resulted in more advantageous reversal times for sugammadex 14 . The incidence of postoperative RNMB with TOF ratios <0.9 or <0.7 was significantly lower in sugammadex-versus neostigmine-or non-reversed (timing) patients 14,16,17 . A significant correlation between RNMB and postoperative chest X-ray pathology was reported in one investigation 16 .…”
Section: Methodsmentioning
confidence: 85%
“…A further study investigating the rate of RNMB at the end of surgery was reported by Von Quillfeldt et al 17 , who describe a smaller observational comparison between 17 patients with a rocuronium/sugammadex combination versus 22 subjects with mivacurium/no reversal. Though surgeons (eye surgery) were 100% satisfied with the operating conditions in both groups, RNMB was frequently observed in the "no reversal", but not the sugammadex group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies demonstrated that sugammadex reverses NMB 3 to 8 times faster than conventional reversal agent does. [ 19 , 20 ] In addition, sugammadex could reduce the incidence of residual NMB, [ 21 ] thus may result in reduced early postoperative pulmonary complications. [ 7 , 22 ] Postoperative residual muscle relaxation is associated with an increased risk of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…123 Sugammadex use enables rapid reversal of deep neuromuscular block to be feasible, and it is this property that is being utilized in many surgical situations, particularly in day case and fast-track procedures, and bariatric, ophthalmic, laparoscopic general, and intra-operative spinal surgery. 124127 There is an indication for sugammadex use to reverse rapidly profound rocuronium blockade post-Caesarean section. 80…”
Section: Clinical Studies (Post-marketing) and Sugammadex Indicationsmentioning
confidence: 99%